Sociological Analysis of â€œMirror Imageâ€ Novel By Sandra Novel - Andriyani, Fitin; Tahrun, Tahrun; Mulyadi, Mulyadi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This research aimed at finding out and developing intrinsic elements and how social life was presented in the novel Mirror Image by Sandra Brown. This is a qualitative research. The data of the research were taken from word, phrase, sentences in the novel and they were analyzed used triangulation method. Data source triangulation was achieved through the inclusion of two different types of data: interviews and questionnaire. The result showed were social aspect, economy aspect, politic aspect, and cultural aspect.